2010
DOI: 10.1111/j.1466-8238.2009.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and controls of the variability of radiation use efficiency and primary productivity across terrestrial ecosystems

Abstract: AimThe controls of gross radiation use efficiency (RUE), the ratio between gross primary productivity (GPP) and the radiation intercepted by terrestrial vegetation, and its spatial and temporal variation are not yet fully understood. Our objectives were to analyse and synthesize the spatial variability of GPP and the spatial and temporal variability of RUE and its climatic controls for a wide range of vegetation types.Location A global range of sites from tundra to rain forest. MethodsWe analysed a global data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
207
8
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(238 citation statements)
references
References 84 publications
15
207
8
8
Order By: Relevance
“…For example, the slope coefficient in the Ball-Berry model (Equation (2)) was estimated as 7.5 to 10.3, consistent with the values in Community Land Model(CLM)4.0 [43]. The estimated maximum light-use efficiency values (0.0011 mg·CO 2 ·µmol −1 PPFD for forest and grassland and 0.0022 mg·CO 2 ·µmol −1 PPFD for cropland) are located in the middle range of ε max variations in the meta-analyses of Kergoat et al [44] and Garbulsky et al [45]. Note that we derived ε max using the NDVI data to estimate FPAR (Equation (3)).…”
Section: Parameters Of the Swh Modelsupporting
confidence: 59%
“…For example, the slope coefficient in the Ball-Berry model (Equation (2)) was estimated as 7.5 to 10.3, consistent with the values in Community Land Model(CLM)4.0 [43]. The estimated maximum light-use efficiency values (0.0011 mg·CO 2 ·µmol −1 PPFD for forest and grassland and 0.0022 mg·CO 2 ·µmol −1 PPFD for cropland) are located in the middle range of ε max variations in the meta-analyses of Kergoat et al [44] and Garbulsky et al [45]. Note that we derived ε max using the NDVI data to estimate FPAR (Equation (3)).…”
Section: Parameters Of the Swh Modelsupporting
confidence: 59%
“…In many cases, a simple APAR green -based model based may be insufficient, particularly for evergreen ecosystems where dynamic light-use efficiency can be an important determinant of CO 2 fluxes and may have to be included in the model [35,74,76]. Additionally, the exact definition and parameterization of the LUE model may itself affect observations regarding light-use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Bandaruet al (2013) found that modeled NPP in Illinois and Iowa were 2.4 and 1.1 times greater than the MODIS GPP/NPP product for corn and soybean, respectively. However, model evaluation did not identify significant biases in other biomes (Sjöström et al, 2013;Turner et al, 2006), which implies that the differences between field and satellite LUE estimates are the most pronounced in croplands (Garbulsky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%